PENGEMBANGAN VIDEO PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA - Luluk Anisatul Farida; Sri Hariyani; Trija Fayeldi (Prodi Pendidikan Matematika FKIP Universitas Madura, 2021)
The purpose of this study is to produce a valid, practical, and effective learning video that can improve cognitive learning outcomes for grade VIII students of Public Junior High School 5 Malang on the Prism dan Pyramid Volume material. The development model used is ADDIE (analysis, design, development, implementation, and evaluation). The quality of the resulting learning video meets the following criteria: a) valid, with an averange score of 3,38 by material experts and media experts; b) practical, with an averange score of teacher response questionnaires and student response questionnaires of 3,50; c) effective, with an averange score of student learning test results of 83,75 and has met the Minimum Completeness Criteria (KKM) at Public Junior High School 5 Malang, namely 78. Thus, it can be conclude that the learning videos developed are valid, practical, and effective to improve cognitive learning outcomes of grade VIII Students of Public Junior High School 5 Malang on prism and pyramid volume material.